KANDUNGAN LOGAM BERAT PADA DAGING DARI SAPI BALI YANG DIGEMBALAKAN DI AREA TEMPAT PEMBUANGAN AKHIR (TPA) - T. S., Undaharta; Ariana, I N. T; Sriyani, N. L. P. (Jurnal Peternakan Tropika; Vol 4 No 2 (2016), 2016)
This study aims to determine the content of heavy metals in bali cattle grazing extensively in the landfill area and semi-intensive outside TPA. The research was conducted in slaughter house traditional as well in Analytical Laboratory Udayana University for two months. The experiment was conducted using a test T-test which two samples were repeated six times. The results showed that the amount content of plumbum, cadmium and cuprum on beef from the landfill quantitatively greater than the beef that comes from outside the landfill 1.559 mg / kg: 1.458 mg / kg, 1.363 mg / kg: 1.358 mg / kg and 1,515 mg / kg: 1.408 mg / kg but in statistics results was not significant (P> 0.05). Based on the results of the study concluded that the system of raising animals do not affect the content of heavy metals in bali cattle, meat from the landfill quantitatively higher than outside the landfill and still be below the threshold recommended by BPOM so it is still suitable for consumption
Keywords: heavy metals, bali cattle, landfill